G135 Associations between GP experience and health outcomes among English adolescents: cross-sectional study of national data. (27th April 2016) - Yassaee, AA; Hargreaves, DS; Lamb, S; Chester, K; Brooks, FM
Abstract : Background: Adolescence is a key stage of the life course when lifelong health behaviours and attitudes to healthcare may be established. Poor experience of GP consultations is common among adolescents, but little is known about whether poor experience in this group is associated with worse health status or outcomes. This study aimed to investigate this association using data from the 2014 Health Behaviour in School-Aged Children (HBSC) survey (England). Methods: We used logistic regression to analyse data on 5335 participants aged 10–17 years in the HBSC survey. Four aspects of recent GP experience were studied: feeling at ease; being treated with respect; quality of GP explanation; and feeling able to talk about personal matters. Five dichotomized measures of health status/outcome were used (ever self-harmed; fair/poor self reported health; frequent (at least weekly) low mood, sleeping problems or headaches). We adjusted for participants' gender, age, ethnicity and family affluence score. Of 5335 participants, 1187 (22.3%) had not visited their GP within the last year and were excluded from the analysis. Findings: In total, 92% of adolescents felt treated with respect, 54% could talk about personal matters, 41% were satisfied with explanations and 31% felt at ease. Participants who reported poorer experience of GP care were more likely to have poor health outcomes. For example, those who did not feel at ease with their GP were more likely to report: self-harm, Adjusted Odds Ratio (AOR) 2.65 (95% CI 1.69–4.15); fair/poor health, AOR 1.64 (1.28–2.10); low mood, AOR 1.51 (1.25–1.82); and sleeping problems, AOR 1.41 (1.19–1.66). All GP indicators were associated with self-harm (AOR range 1.64–2.70, GP's explanation: p = 0.006, all others: p < 0.001) and feeling low (AOR range 1.46–2.11, all p < 0.001). The association with GP experience was less consistent for the other three health outcomes. Interpretation: This cross-sectional, observational study demonstrates that young people who report worse health symptoms, typically also report a poorer experience of care. Further research is needed to investigate whether GP experience influences health outcomes – suggesting that improving GP experience may improve health outcomes in this group – or whether poor health status leads to more negative perceptions of care.